PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII UPT SMP NEGERI 1 KOTO XI TARUSAN - Kurnia, Eriska; Abdurrahman, Abdurrahman (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study is three. First, describing the skill of writing fable texts of VII grade students of UPT SMP Negeri 1 Koto XI Tarusan before using discovery learning models assisted by audiovisual media. Second, describing the skill of writing fable texts of VII grade students of UPT SMP Negeri 1 Koto XI Tarusan after using discovery learning models assisted by audiovisual media. Third, describing the influence of discovery learning models assisted by audiovisual media on fable text writing skills of seventh grade students of UPT SMP Negeri 1 Koto XI Tarusan. This type of research is quantitative research with experimental methods. The design of this study was one group pretest and posttest design. The population in this study were 167 students. The sample in this study were 28 students who were determined using purposive sampling technique. The variable of this research is fable text writing skills before and after using the discovery learning learning model assisted by audiovisual media of VII grade students of UPT SMP Negeri 1 Koto XI Tarusan. The instrument of this research is the performance test. The results of this study are three, namely as follows. First, fable text writing skills before using the discovery learning model assisted by audiovisual media of VII grade students of UPT SMP 1 Koto XI Tarusan are more than Sufficient (LdC) qualifications with an average of 72.62. Second, fable text writing skills after using the discovery learning model assisted by audiovisual media in seventh grade students of UPT SMP 1 Koto XI Tarusan are in a Good qualification (B) with an average of 81.25. Third, based on the t-test, the alternative hypothesis (H_1) is received at a significant level of 95% and the degree of freedom (dk) = n-1 because of tcount> t table, which is 2.73> 1.70.Â Kata Kunci: pengaruh, model discovery learning, keterampilan menulis teks fabel.